Hyperperfusion Tmax mapping for nonconvulsive status epilepticus in the acute setting: A pilot case–control study. Issue 10 (20th July 2022) - Romoli, Michele; Merli, Elena; Galluzzo, Simone; Muccioli, Lorenzo; Testoni, Stefania; Zaniboni, Anna; Contardi, Sara; Simonetti, Luigi; Tinuper, Paolo; Zini, Andrea
Abstract: Objective: Nonconvulsive status epilepticus (NCSE) is misdiagnosed in >50% of cases in the emergency department. Computed tomographic perfusion (CTP) has been implemented in the hyperacute setting to detect seizure‐induced hyperperfusion. However, the diagnostic value of CTP is limited by the lack of thresholds for hyperperfusion and high interrater variability. This pilot case–control study aims at identifying the diagnostic value of reverse Tmax (rTmax) in differentiating NCSE from acute ischemic stroke in the hyperacute setting. Methods: We enrolled patients with NCSE (Salzburg criteria‐based diagnosis) and stroke cases 1:1 matched for clinical features and time of presentation. CTP standard maps (mean transit time [MTT]–cerebral blood volume–cerebral blood flow [CBF]) and rTmax maps were elaborated and rated by two experts in CTP blinded to the final diagnosis. Hyperperfusion was adjudicated for standard CTP maps as an increase in CBF and a decrease in MTT, and for rTmax as the presence of a black area on 3‐, 2‐, and 1‐s threshold maps. Cronbach alpha was used for interrater agreement; receiver operating curve analysis was run to measure accuracy with area under the curve. Results: Overall, 34 patients were included (17 NCSE, 17 stroke; time from onset to imaging = 2 h for both groups). People with NCSE were older and more frequently had a history of epilepsy. NCSE patients had hyperperfusion on rTmax maps in 11 of 17 cases versus zero of 17 in stroke. Intra‐ and interrater reliability was higher for rTmax than for standard CTP maps ( κ  = 1 vs. κ  = .6). rTmax was 82% (95%CI = 67–97%) accurate in predicting NCSE versus stroke in the hyperacute setting. Agreement between neuroimaging and electroencephalography (EEG) was limited at a hemispheric level for standard CTP maps, whereas rTMax had agreement with EEG largely reaching the sublobar level. Significance: rTmax mapping might represent a reliable tool to spot NCSE‐induced hyperperfusion with a threshold‐based reproducible approach. Further studies are needed for validation and implementation in the differential diagnosis of focal neurological deficit in the hyperacute setting.